2015
DOI: 10.9767/bcrec.10.3.8824.313-323
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Mesoporous Polymer Matrix Nature on the Formation of Catalytically Active Ruthenium Nanoparticles

Abstract: This paper reports on ruthenium nanoparticles formation and stabilization by hypercrosslinked polystyrene and the catalytic properties of the nanocomposites obtained. Hypercrosslinked polystyrene with functional groups and without them was used. The nanocomposites were characterized using lowtemperature nitrogen physisorption, X-ray photoelectron spectroscopy and transmission electron microscopy. It is established that the tertiary amine group of the support influences both formation of ruthenium nanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…The catalyst was used in the oxidation of L-sorbose to 2-keto-L-gulonic acid, demonstrating selectivity for the target product of 98% at 100% conversion. Further studies on the synthesis of catalysts based on commercial HPS, namely micro/macroporous Macronet NM (Purolite, Llantrisant, UK), and different noble metals, showed that the catalytic activity of such systems depends, in particular, on the presence of macropores [88], chemical nature of the precursor of the active phase [89], the presence of functional groups in the HPS [90], and the type of solvent used for the reaction [91]. In general, such catalytic systems have shown higher efficiency as compared to the catalysts with traditional catalytic supports [29].…”
Section: Hypercrosslinked Polystyrene In Heterogeneous Catalysismentioning
confidence: 99%
“…The catalyst was used in the oxidation of L-sorbose to 2-keto-L-gulonic acid, demonstrating selectivity for the target product of 98% at 100% conversion. Further studies on the synthesis of catalysts based on commercial HPS, namely micro/macroporous Macronet NM (Purolite, Llantrisant, UK), and different noble metals, showed that the catalytic activity of such systems depends, in particular, on the presence of macropores [88], chemical nature of the precursor of the active phase [89], the presence of functional groups in the HPS [90], and the type of solvent used for the reaction [91]. In general, such catalytic systems have shown higher efficiency as compared to the catalysts with traditional catalytic supports [29].…”
Section: Hypercrosslinked Polystyrene In Heterogeneous Catalysismentioning
confidence: 99%
“…Next article was focused on influence of the mesoporous polymer matrix nature on the formation of catalytically active ruthenium nanoparticles by Sulman et al [11]. They reported about ruthenium nanoparticles formation and stabilization by hypercrosslinked polystyrene and the catalytic properties of the nanocomposites obtained.…”
Section: Bulletin Of Chemical Reaction Engineering and Catalysis 10 (3mentioning
confidence: 99%
“…The deoxygenation of fatty compounds is an efficient route for green diesel production using heterogenized catalysts supported on zeolites and others [19][20][21]. Hypercrosslinked polystyrenes (HPS), or functionalized polystyrenes (such as amine-functionalized), are useful in the stabilization of metallic nanoparticles and clusters [22][23][24][25]. The stabilization of nanoparticles is vital for the production of ruthenium mono and bimetallic catalysts applicable in biorefinery processes, such as the oxidation and hydrogenation of glucose, the hydrogenolysis of cellulose, on Suzuki cross-coupling and on the lactic acid hydrogenation [26][27][28].…”
Section: Introductionmentioning
confidence: 99%